Analisis Perbandingan Tingkat Pengungkapan CSR BUS Indonesia Berdasarkan Indeks ISR dan SET: Analisis Perbandingan Tingkat Pengungkapan CSR BUS Indonesia Berdasarkan Indeks ISR dan SET - Atiqah, Nur; Verdianti, Verdianti; Ramadhanti, Ade Ira (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2020)
This study determine disclosure level of Corporate Social Responsibility among Islamic Commercial Banks in Indonesia based on Islamic Social Reporting Index and Sharia Enterprise Theory approaches, and comparison disclosure level of Corporate Social Responsibility among Islamic Commercial Banks in Indonesia. In this study, CSR disclosure based on the Islamic Social Responsibility Index uses 80 sub-themes with 6 themes, such as theme of funding and investment, theme of products and services, theme of labor, theme of society and theme of organizational governance while Sharia Enterprise Theory uses 21 sub-themes with 5 themes, such as accountability to Allah SWT, accountability to customers, accountability to employees, accountability to community, and accountability to nature. The sample in this study amounted to 14 Islamic commercial banks in Indonesia in 2017 and 2018 reporting periods. Data was analyzed using content analysis and independent t-test. Results of this study indicate that (1) the level of Corporate Social Responsibility disclosure among Islamic Commercial Banks in Indonesia based on the Islamic Social Reporting Index has an average 72.5% (informative), and the level of Corporate Social Responsibility disclosure among Islamic Commercial Banks in Indonesia based on Sharia Enterprise Theory has an average 70% (informative). (2) The level of disclosure of Corporate Social Responsibility of Islamic Commercial Banks in Indonesia based on the Islamic Social Reporting Index and Sharia Enterprise Theory shows no significant difference at 5% significance level.